The prognostic value of sentinel lymph nodes on distant metastasis–free survival in patients with high-risk squamous cell carcinoma. (April 2019) - Jansen, Philipp; Petri, Maximilian; Merz, Simon F.; Brinker, Titus J.; Schadendorf, Dirk; Stang, Andreas; Stoffels, Ingo; Klode, Joachim
Abstract: Background: Cutaneous squamous cell carcinoma (cSCC) is the second most common cutaneous cancer worldwide. Several tumour characteristics are considered to pose an elevated risk for systemic spread of carcinoma cells ('high-risk' features). Early detection of subclinical metastases could permit early treatment and improve overall survival. To detect occult metastases and evaluate risk of future distant metastases, diagnostic extirpation of the sentinel lymph node (SLNE) is routinely performed in cutaneous melanoma and can be offered in high-risk cutaneous squamous cell carcinoma (hrcSCC). However, the clinical utility of SLNE in patients with hrcSCC remains unknown. Material and methods: An ambidirectional cohort study with prospective patient recruitment was performed. Between July 2008 and April 2017, of 139 eligible patients, SLNE was performed in 114 cases (25 patients refused). Median follow-up was 23.7 months. Results: We analysed the characteristics of 114 patients with hrcSCC who underwent SLNE. Eighty-nine patients (78.1%) were men, and 25 patients (21.9%) were women (median age 72.2 years). In multivariable analyses, histopathological detection of ulceration (hazard ratio, HR 2.9 [95% confidence interval, CI 0.7–12.2]), perineural growth (HR 3.0 [95% CI 0.6–14.6]) and clinically occult SLN metastases (HR 10.7 [95% CI 1.9–60.6]) were strongly associated with future occurrence of distant metastases. A positive predictive value of 50% was noted for patients where SLN metastasis was detected to develop distant metastases. However, distant metastases also occurred in seven patients when histopathological SLN evaluation had shown no evidence of metastases. Conclusions: Our data suggest SLNE is not a reliable diagnostic approach to evaluate the risk of future systemic carcinoma spread and development of distant metastases in patients with hrcSCC. Highlights: Cutaneous squamous cell cacrinoma (cSCC) is the second most common skin cancer after basal cell carcinoma. The risk to metastasise is markedly elevated for cSCCs with a tumor depth > 4 mm, undifferentiated or perineural growth. The value of sentinel lymph node ex in hrcSCCs is highly controversial.